STAD DENGAN GEOGEBRA UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA SMA - , M.Si, Ismiati (Universitas Islam Balitar, 2021)
The purpose of this research is to improve student learning outcomes. The indicators of success used are test results, and individual quiz results at the end of each lesson. The research design carried out on researchers refers to the Kemmis and Taggard model. STAD with Geogebra implemented using the help of whatsapp and google form. The research subjects were students of class XII IPA-4 at SMAN 1 Kademangan in the Odd Semesters of the 2020/2021 Academic Year. The results of the study in cycle 1 showed that there was an increase in learning outcomes even though not all met the success criteria, from the test results obtained the percentage of success classically 58,8% and from the average process of individual quiz success at the end of each meeting obtained 81,36% In the second cycle the percentage of success of the test results obtained 85,3% while the average percentage of success of individual quizzes at the end of each meeting was 86,3. From these data STAD with Geogebra accompanied by the use of whatsapp and google form can improve student learning outcomes for class XII IPA 4 on trigonometry application material. It is hoped that with this research the teacher can apply it to other materials that have the same characteristics so that they can improve overall mathematics learning outcomes.